Incidence and risk factors for acute kidney injury in children with nephrotic syndrome: a meta-analysis - Chen, Changdi; Qiu, Bingbing; Wang, Jianxin; Yang, Liuqing; Huang, Yanru (Frontiers in Pediatrics, 2024)
Background Nephrotic syndrome (NS) is a prevalent kidney disease in children. Acute kidney injury (AKI) is a severe complication of NS and has the potential to be life-threatening. Objective The aim of this study was to analyze the prevalence and risk factors of AKI in children with NS, and to provide an evidence-based medical basis for the early identification of high-risk children in the clinic. Methods A comprehensive search was conducted in publicly available databases, namely PubMed, Embase, Web of Science, Scopus, and the Cochrane Library, covering the period from the inception of each database until May 2024. The analysis involved examining basic characteristics (age, sex), the concomitant diseases (hypertension, infections), NS disease characteristics (steroid susceptibility classification, pathologic classification), laboratory test (e.g., serum albumin), and the use of nephrotoxic drugs. Traditional and network meta-analyses were performed for analysis. Results A total of 11 studies were included in the analysis, revealing an incidence of AKI of 29% (95% CI: 23%–37%). The analysis of factors indicated that the age of NS onset [standardized mean difference (SMD): 0.31; 95% confidence interval (CI): 0.08, 0.54; p = 0.009], sex [odds ratio (OR): 1.49; 95% CI: 1.03, 2.16; p = 0.035], serum albumin level (SMD: −0.43; 95% CI: −0.85, −0.02; p = 0.041), response to steroid treatment (OR: 0.52; 95% CI: 0.33, 0.80; p = 0.003), infection (OR: 3.60; 95% CI: 1.91, 6.78; p < 0.001), hypertension (OR: 4.02; 95% CI: 2.94, 5.51; p < 0.001), and nephrotoxic drug application (OR: 4.43; 95% CI: 1.86, 10.53; p = 0.001), were all significantly associated with the incidence of AKI. Furthermore, the results of the network meta-analysis suggested that the pathologic type of minor glomerular abnormalities (MGA)/diffuse mesangial proliferation (DMP), the type of infrequent relapses (IFRNS)/steroid-sensitive NS (SSNS), and the use of diuretic medications were associated with a relatively low risk of AKI occurrence. Conclusion Factors upon admission of children with NS are associated with the onset of AKI. Emphasis should be placed on populations with a heightened risk of AKI in clinical practice. Further research is warranted to confirm the findings due to the limitations of this study. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024571170, PROSPERO (CRD42024571170).